y=9mx-3b

Rewrite the equation as 9mx-3b=y.

9mx-3b=y

Add 3b to both sides of the equation.

9mx=y+3b

Divide each term in 9mx=y+3b by 9m.

9mx9m=y9m+3b9m

Simplify 9mx9m.

Cancel the common factor of 9.

Cancel the common factor.

9mx9m=y9m+3b9m

Rewrite the expression.

mxm=y9m+3b9m

mxm=y9m+3b9m

Cancel the common factor of m.

Cancel the common factor.

mxm=y9m+3b9m

Divide x by 1.

x=y9m+3b9m

x=y9m+3b9m

x=y9m+3b9m

Cancel the common factor of 3 and 9.

Factor 3 out of 3b.

x=y9m+3(b)9m

Cancel the common factors.

Factor 3 out of 9m.

x=y9m+3(b)3(3m)

Cancel the common factor.

x=y9m+3b3(3m)

Rewrite the expression.

x=y9m+b3m

x=y9m+b3m

x=y9m+b3m

x=y9m+b3m

Solve for x y=9mx-3b